Architectural Decoding and Analysis of the Krishnabai Temple in Mahabaleshwar, India: A Comprehensive Documentation Study - Shreya Parikh; Archana Baghel (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This research paper represents a detailed documentation study and architectural analysis of Krishnabai temple, located in Mahabaleshwar, India. The temple is built in the Hemadpanti style of Architecture, which celebrates the origin of River Krishna and hence gets its name from. The paper focuses on the architectural nuances of this ancient monument like its form, spatial order, built character, construction systems, details etc. The paper investigates the historic and physical features of this structure through a systematic survey and detailed architectural documentation. Inspite of being an ASI -protected monument, the structure is under the threat of decay and anthropogenic destruction without an effort of conservation and less maintenance. Moreover, this research will lay a foundation for future conservation work for the monument and also will contribute to the study of the historic temple architecture of India.